Indonesian Criminal Code Draft (RKUHP) Objectivity on Tirto.id - Amal, Muhammad Ihlasul; Mursalim, Mursalim; Karnay, Sudirman (Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to determine the tendency of Tirto.id as one of the cyber media to present news on the Indonesian Criminal Code Draft (RKUHP). This research uses Westerståhl’s objectivity framework to measure Tirto’s objectivity in presenting coverage of the RKUHP. Westerståhl divides objectivity into two large dimensions, namely factuality and impartiality. The factuality dimension consists of aspects of truth and relevance, while the impartiality dimension consists of balance/non-partisanship aspects. The primary data for this research is news published by Tirto.id which discusses the RKUHP in the period May-September 2019 with a total of 118 news. News is searched using the keyword “RKUHP 2019”. The news was documented and samples were drawn using total sampling, so that the population is the sample for this research. The news was then analyzed using the content analysis method. This research shows that Tirto.id generally tends to report on the RKUHP objectively. Tirto.id fulfills the aspects of truth, relevance and neutrality with a very high percentage of all criteria in each of these aspects. Meanwhile, the balance aspect tends not to be fulfilled by Tirto.id in terms of equal or proportional access criteria. However, Tirto.id tends to present news from various sides of reporting (positive, negative and neutral) which are contained in two-sided criteria (even handed) in a balanced aspect. Keywords: objectivity, news, RKUHP, Tirto.id, Westerståhl